An Extension of the Eindhoven Classification Model to the Educational Sector - Figueiredo, Margarida (2013)
This work presents an extension of the Eindhoven Classification Model to sort adverse events root causes for the Educational Sector. Extended Logic Programming was used for knowledge representation and reasoning with defective information, allowing for the modelling of the universe of discourse in terms of default data, information and knowledge. Indeed, a systematization of the evolution process of the body of knowledge in terms of Quality of Information (QoI) embedded in the Root Cause Analysis was accomplished, i.e., the knowledge representation and reasoning system proposed led to a process of QoI quantification that allowed the study of the event's root causes, on the fly.